HEALTH SEEKING BEHAVIOURS OF SCIENCE STUDENTS AND THEIR PERCEPTION OF HEALTH CARE SERVICES IN THE UNIVERSITY OF EDUCATION, WINNEBA - Koomson, Charles Kwesi (International Journal of Public Health Science (IJPHS), 2020)
The study seek to investigate the health seeking behaviour of undergraduate students in the University of Education, Winneba and their perception of health care services rendered to them at the various health centers in Winneba. The study sampled 540 undergraduate students from the Faculty of Science Education in the University and their responses where collected using a structured questionnaire items. Data collected from this study were analysed using descriptive statistics. It was evident that majority of the respondents (84.4%) never experience any illness whilst on campus. The few that experienced some forms of illness also did not visit the hospitals for treatment. Majority preferred pharmaceutical drugs for treatment. Other respondents also resorted to the use of herbs for treatment because according to them, herbal medicine is much effective, easily accessible and also do not waste time when one wanted to access them. The study recommended that students should make it a habit of visiting the hospitals in and around campus whenever they experience any form of symptoms and should not resort to self-medications which could have detrimental effect on their health. University hospital staff should also render faster services to students to make them have time for their academic work. Key words: Health, Students, Behaviour, Hospital, University